Interventions in cytokine signaling: novel horizons for psoriasis treatment - Li, Lisha; Liu, Jun; Lu, Jiaye; Wu, Junchao; Zhang, Xinyue; Ma, Tianyou; Wu, Xiying; Zhu, Quangang; Chen, Zhongjian; Tai, Zongguang (Frontiers in Immunology, 2025)
Intricate interactions between immune cells and cytokines define psoriasis, a chronic inflammatory skin condition that is immunological-mediated. Cytokines, including interleukins (ILs), interferons (IFNs), tumor necrosis factors (TNFs), chemokines, and transforming growth factor-β (TGF-β), are essential for controlling cellular activity and immunological responses, maintaining homeostasis and contributing to the pathogenesis of psoriasis. These molecules modulate the immune microenvironment by either promoting or suppressing inflammation, which significantly impacts therapeutic outcomes. Recent research indicates that treatment strategies targeting cytokines and chemokines have significant potential, offering new approaches for regulating the immune system, inhibiting the progression of psoriasis, and reducing adverse effects of traditional therapies. This review consolidates current knowledge on cytokine and chemokine signaling pathways in psoriasis and examines their significance in treatment. Specific attention is given to cytokines like IL-17, IL-23, and TNF-α, underscoring the necessity for innovative therapies to modulate these pathways and address inflammatory processes. This review emphasizes the principal part of cytokines in the -pathological process of psoriasis and explores the challenges and opportunities they present for therapeutic intervention. Furthermore, we examine recent advancements in targeted therapies, with a particular focus on monoclonal antibodies, in ongoing research and clinical trials.